Microsatellites for the Neotropical Ant, Odontomachus chelifer (Hymenoptera: Formicidae). Issue 5 (24th October 2020) - Lemos, Alessandra S M; Azevedo-Silva, Marianne; Gonçalves-Neto, Salatiel; Souza, Anete P; Oliveira, Paulo S
Abstract: Odontomachus chelifer (Latreille) (Ponerinae) is a ground-dwelling, predominantly carnivorous ant whose colonies may contain multiple egg-laying queens and are potentially susceptible to border effects in the Brazilian savanna known as Cerrado. The ecology and natural history of O. chelifer is well studied, but very little is known about the genetic diversity of O. chelifer colonies. In this study, we developed microsatellite markers for the study of genetic variation in O. chelifer . We created a microsatellite-enriched library that resulted in the development and characterization of 22 markers, of which 18 were found to be polymorphic in the population studied. The mean expected heterozygosity was 0.59, whereas the mean rarified allelic richness was determined as 4.27 alleles per locus. The polymorphism level detected was similar to genetic diversity estimates found in other poneromorph ant species. The microsatellites developed here are likely to be useful for the investigation of colony structure, functional polygyny, breeding system, and population genetics in O. chelifer . Moreover, the description of O. chelifer 's genetic diversity is crucial for its conservation and maintenance of its ecological role in the Cerrado savanna.